Kinetics studies and thermodynamics of oil extraction from immobilized microalgae cells of Chlorella vulgaris: The effect of the different matrix system - Nagaarasan, Ramesh; Nur Hidayah, Mat Yasin; Zatul Iffah, Mohd Arshad (IOP Publishing, 2020)
This research article discusses the effect of different chemical matrices used for the immobilization of microalgae cells of Chlorella vulgaris on oil extraction in terms of oil yield, kinetic values, and thermodynamic values. The experimental procedures began with microalgae cultivation, immobilization of microalgae, microalgae harvesting, and oil extraction. For the immobilization method, the matrix systems involved were sodium alginate (SA), calcium alginate (CA), and sodium carboxymethyl cellulose (CMC). For the oil extraction process, heptane was used as an only solvent at different temperature and extraction time. The amount of oil extracted from the SA system was found to be the highest compared to other chemical matrix systems, which is 25.11 % at 348 K. The values of the reaction rate constants were found to increase with temperature and extraction time for SA and the activation energy was determined to be 39.6636 kJ/mol, which is lowest among the systems. Moreover, with the enthalpy value of 0.115 kJ/mol, the extraction process using the SA system is endothermic and was found to be industrially more feasible process compared to other matrix systems. Hence, the results proved that the immobilization of microalgae for biodiesel production is considerable for the future biofuel industry.